Internet Gaming Disorder: An Emerging Addiction among Pakistani University Students - Sadaf Zahra; Shoaib Kiani; Kanwal Shahbaz (NUST Journal of Social Sciences and Humanities)
Internet gaming is increasing day by day with technology development. Today occurrence of IGD and its relationship with certain demographic variable will be viewed. Through the convenient sampling technique the study consisted of a sample of 315 university students of graduation level of education. The 20 item IGDT-20 was used to measure IGD. The analysis plan included correlation, t-test and ANOVA for hypothesis testing. The results indicated that males scored higher on Internet Gaming Disorder scale than females; young students spend more time on internet than others and are at high risk of developing Internet Gaming Disorder. These findings are helpful in developing a policy for the effective use of internet.